Engineering Hybrid Quantum Systems: Strong Coupling Between Nitrogen-Vacancy Centers and a Superconducting Resonator - Herri Trisna Frianto; Ming Pong; Rit Som (Yayasan Adra Karima Hubbi, 2025)
Hybrid quantum systems that integrate solid-state qubits with superconducting circuits have emerged as a promising architecture for scalable quantum information processing. Achieving strong coherent coupling between distinct quantum subsystems, such as spin ensembles and microwave resonators, remains a critical challenge in realizing hybrid quantum technologies. This study aims to engineer and characterize a hybrid platform that couples nitrogen-vacancy (NV) centers in diamond with a superconducting coplanar waveguide resonator. A combination of cryogenic microwave spectroscopy and time-domain measurements was employed to evaluate coupling strength, coherence times, and collective spin photon interactions at millikelvin temperatures. The experimental results demonstrated a vacuum Rabi splitting of 22 MHz, confirming the realization of a strong coupling regime between the NV spin ensemble and the superconducting resonator. The coherence lifetime of the NV centers remained above 100 ?s under optimized magnetic field alignment, ensuring stable quantum-state transfer. The findings reveal that hybrid systems combining spin-based and superconducting components can serve as viable interfaces for quantum memory and quantum communication nodes. The study concludes that engineering such strong spin–photon coupling represents a foundational step toward the development of coherent, scalable hybrid quantum networks.